2020
DOI: 10.3390/nu12092609
|View full text |Cite
|
Sign up to set email alerts
|

Use of Plastics with Hot Food among Saudi Pregnant Women Is Associated with Increased Concentrations of A1C, Thyroid-Stimulating Hormone, and Homocysteine and Decreased Concentrations of Vitamins and Minerals

Abstract: Data regarding association between the use of plastics with hot food and levels of vitamins and minerals, and other biochemical parameters are lacking. Cross-sectional data for 740 healthy pregnant Saudi women were collected from 21 health care centres and 2 hospitals from Madinah, Saudi Arabia. Detailed data regarding the frequency of plastic use with hot food were collected, and laboratory analyses of thyroid-stimulating hormone (TSH), homocysteine (HCY), glycated A1C (A1C), and selected vitamins and mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Regarding practice assessment items, approximately 76.5% of our study participants used plastic containers for hot foods or drinks with variable frequency. Similarly, Alharbi et al ( 25 ), in their study that involved Saudi pregnant women, observed that almost 70% of the participants reheat or buy hot food in plastic containers. Additionally, we found that more than 90% of our study participants reused plastic bottles for saving and drinking water.…”
Section: Discussionmentioning
confidence: 87%
“…Regarding practice assessment items, approximately 76.5% of our study participants used plastic containers for hot foods or drinks with variable frequency. Similarly, Alharbi et al ( 25 ), in their study that involved Saudi pregnant women, observed that almost 70% of the participants reheat or buy hot food in plastic containers. Additionally, we found that more than 90% of our study participants reused plastic bottles for saving and drinking water.…”
Section: Discussionmentioning
confidence: 87%